Effects of soil preparation, food availability, and temperature on survival of Agriotes obscurus (Coleoptera: Elateridae) larvae in storage. Issue 6 (11th May 2016) - van Herk, Wim; Vernon, Bob; Perry, Alison; Ryan, Kathryn; Chee, Andrea
Abstract: Field collected wireworms (Coleoptera: Elateridae) intended for laboratory studies often die during storage from Metarhizium Sorokin (Clavicipitaceae) infection and other causes. To determine optimal storage conditions for Agriotes obscurus (Linnaeus), freshly collected larvae were stored in regular and sterilised soil, with and without access to food (potato slices), at 12 °C and 16 °C, for six months to determine which conditions resulted in the lowest wireworm mortality. Survival was highest when wireworms were stored in sterilised soil, at 12 °C, in the absence of food. Food availability increased wireworm mortality from Metarhizium infection and other causes, but decreased the number of missing wireworms. Wireworm weight change during the study was highest in treatments where wireworms had access to food. The expected effect of food deprivation on wireworm energetic state and immune response are discussed in context with these findings.